Anti-inflammatory effects of thymol: an emphasis on the molecular interactions through in vivo approach and molecular dynamic simulations - Islam, Muhammad Torequl; Bappi, Mehedi Hasan; Bhuia, Md Shimul; Ansari, Siddique Akber; Ansari, Irfan Aamer; Shill, Manik Chanda; Albayouk, Tala; Saleh, Na’il; El-Shazly, Mohamed; El-Nashar, Heba A. S. (Frontiers in Chemistry, 2024)
Thymol (THY), as the natural monoterpene phenol, acts against oxidative stress and inflammatory processes. This study aimed to evaluate the anti-inflammatory effects and possible molecular mechanisms of THY via formalin-induced mouse and egg albumin-induced chick models alongside molecular docking and molecular dynamic (MD) simulations. THY (7.5, 15, and 30 mg/kg) was investigated, compared to celecoxib and ketoprofen (42 mg/kg), as anti-inflammatory standards. THY dose-dependently and significantly (p < 0.05) decreased paw-licking and edema diameter parameters in formalin (phases I and II) and egg albumin-induced models. Moreover, THY (15 mg/kg) exerted better anti-inflammatory effects in combination with the standard drug ketoprofen than alone and with celecoxib. In silico studies demonstrated elevated binding affinities of THY with cyclooxygenase-2 (COX-2) than the COX-1 enzyme, and the ligand binds at a similar location where ketoprofen and celecoxib interact. The results of MD simulations confirmed the stability of the test ligand. THY exerted anti-inflammatory effects on Swiss mice and young chicks, possibly by interacting with COX-2. As a conclusion, THY might be a hopeful drug candidate for the management of inflammatory disorders.